You can't put the genie back in the bottle: on the legal and conceptual understanding of genetic privacy in the era of personal data protection in Europe (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
This article sheds a light on how the data protection requirements enshrined in the General Data Protection Regulation (GDPR) relate to shaping genetic privacy in the context of a complex and integrated genetic testing enterprise. It suggests that the informational dimension of genetic privacy in the era of data protection could be described as a sphere of controlled access. Given that the GDPR does not prescribe quantitative or contextual limitations relating to access once the applicable requirements are met, one could argue that there are good preconditions for the field to head in the direction of genetic transparency. This puts on the agenda the questions of what challenges this could bring and whether adequate mechanisms exist to deal with them.
Keywords: Genetic data protection; genetic privacy; genetic testing; scientific publication; scientific research